An Overview of Some Plant Based Products With Hepatoprotective Activity - Labhade, Sonali Dnyaneshwar (Iraqi Journal of Pharmaceutical Sciences, 2021)
In folk medicine there are various medicinal amalgamation possessing hepatoprotective activity. This activity is of significance because several toxins cause liver injury. Hence, many pharmaceutical companies are targeting herbal medicines for the treatment of liver abnormalities and towards evolving a safe and effective formulation with desired route of administration. In current review we have focused on the studies showing hepatoprotective effect using marine compounds and plant derived compounds. Liver disorder, a global health problem, usually include acute or chronic hepatitis, heptoses, and cirrhosis. It may be due to toxic chemicals and certain antibiotics. Uncontrolled consumption of alcohol also affects liver in an unhealthy way. To cure liver disorders several formulations of medicinal plants are being used. It is observed that hepatoprotective effect of plant is mostly due to flavonoids, alkaloids, terpenoids, steroids, and glycoside. A single drug cannot be useful for all the types of liver disorders. Several plant extracts for liver illness results from poisonous chemicals, viruses, extra alcohol consumption, and repeated administration of medication. By using standards of protection and efficacy, manufacture of plant products need to be ruled out. Current review provides an understanding of ethnopharmocology, toxicology of several medicinal plants manifesting hepatoprotective potential. Despite of varied database analysis new discoveries and their probabilities, evidences on viral hepatitis treatment or liver cirrhosis is inadequate. Further information about phytotherapy, toxicology, quality control studies shall be endorsed. Further in depth studies are required to discover quality trait like SAR, MOA, safety and toxicity and therapeutic potential of phytoconstituents in clinical settings.